2013
DOI: 10.5901/jesr.2013.v3n2p397
|View full text |Cite
|
Sign up to set email alerts
|

Comparative Analysis of the Reliability and Validity Coefficients of WAEC, NECO and NABTEB Constructed Mathematics Examination

Abstract: This study compared the reliability and validity co-efficient of mathematics examinations constructed by the

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
2
3

Year Published

2019
2019
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(7 citation statements)
references
References 1 publication
2
2
3
Order By: Relevance
“…This means that the two tests are similar and parallel. It corroborates the findings of Bandele and Adewale (2013) who concluded that WAEC, NECO and NABTEB tests are similar and equivalent.…”
Section: Results Discussion and Suggestionssupporting
confidence: 91%
See 1 more Smart Citation
“…This means that the two tests are similar and parallel. It corroborates the findings of Bandele and Adewale (2013) who concluded that WAEC, NECO and NABTEB tests are similar and equivalent.…”
Section: Results Discussion and Suggestionssupporting
confidence: 91%
“…For multiple choice test, specifically WAEC uses 50 items with each item placed under four response format A, B, C and D, while NECO uses 60 items with each item placed under five response mode, A, B, C, D and E. For the essay tests also known as constructed-response mode and called Paper II, WAEC uses 13 items while NECO uses 12 items. Bandele and Adewale (2013) concluded that WAEC, NECO and NABTEB mathematics achievement examinations are highly reliable and valid and are as well comparable and equivalent. In the aforementioned study multiple choice items were used but this present study will further confirm if WAEC and NECO constructedresponse mathematics items are similar or comparable.…”
Section: Introductionmentioning
confidence: 97%
“…This findings lay credence to the findings of studies carried out by Kolawole (2007); Alfred (2013); Metibemu (2016) and Ogbebor (2017) which says that there was no significant difference between the difficulty level of WAEC and NECO multiple-choice items in mathematics. However, the study disagrees with the submission of Adewale (2008); Bandele and Adewale (2013) and Thomas et al (2016) that NECO examinations are more difficult than WAEC test items. More so, the study disagree with the findings of Abiri (2006) and Olutola (2015) which say 10 difficulty indices of multiple choice test with a fewer number of options say four differ significantly to anyone with a larger number of options.…”
Section: Discussioncontrasting
confidence: 75%
“…This finding is not in line with Obinne (2012) observed that more of the Biology test items constructed by the WAEC were found to be prone to guessing than those items of NECO. This finding is also not in line with Bandele & Adewale's (2013) submission that NECO examinations are more difficult than that of WAEC and NABTEB.…”
Section: Discussioncontrasting
confidence: 64%